ANALYSIS DISCOURSE DEIXIS EKSOFORIS IN THE DAILY ALERT, ANALYSIS, AND FIELD BUSINESS YEAR 2014 - Tri Indah Kusumawati (VISION, 2016)
This study entitled "Analysis of Deixis Eksoforis In Discourse On the Daily Alert, 2014". This study aimed to describe the form of Deixis Eksoforis which examines deixis persona, temporal, locative, and social. As well as analyzing the more dominant forms of deixis appears in discourse analysis.    Sample data will be analyzed based on five types of themes: education, law, corruption, health, and religion published in the daily discourse on Alert edition from June to August 2014. Thus, the number of objects of research amounted to 5 discourse. This research uses descriptive method, a method that describes the data naturally and what it is.    Based on the five themes are analyzed, it can be seen that deixis persona most commonly found in every discourse, totaling 78 words (54.9%). Furthermore, social deixis totaling 35 words (24.6%), then the locative deixis amount to 22 words (15.4%), and the latter temporal deixis amounted to 7 words (4.9%) of 142 sentences were analyzed.Keywords: persona, temporal, locative, social